The Black loyalists : the search for a promised land in Nova Scotia and Sierra Leone, 1783-1870 - Walker, James W. St. G., 1940- (Reprints in Canadian history., 1992)
There is a Canadian myth about the Loyalists who left the United States after the American Revolution for Canada. The myth says they were white, upper-class citizens devoted to British ideals, transplanting the best of colonial American society to British North America. In reality, more than 10 per cent of the Loyalists who came to the Maritime provinces were black and had been slaves. The Black Loyalists tells the story of one such group who came to Nova Scotia, but didn't stay. James Walker documents their experience in Canada, following them across the Atlantic as they became part of a unique colonial experiment in Sierra Leone.